President of the whole sixth grade - Winston, Sherri (Little, Brown and Company, 2015)
Brianna Justice is the president of her Detroit middle school's sixth grade, but she is finding the position a real headache--beside the normal troubles of being in a new school, and the sudden coldness of her old friends, there is a class trip to Washington, D.C. coming up and she needs to figure out how to raise the rest of the money so that the class can go.